Efektifitas Modul Biologi Terintegrasi Kearifan Lokal Minangkabau Berbantuan Model Problem Based Learning (PBL) - Rahmadini, Rahmadini; Marneli, Diyyan; Mardatillah, Annisa; Delfita, Rina; Syafitri, Mardian (Edusainstika: Jurnal Pembelajaran MIPA, 2024)
This research is motivated by teachers who have not designed teaching modules independently, then the students' lack of knowledge about Minangkabau local wisdom and then teachers also have not used the Problem Based Learning (PBL) learning model. learning model which causes the students' learning process to be less capable in solving problems. This research aims to evaluate the effectiveness of using an integrated biology module with Minangkabau local wisdom in the application of the Problem Based Learning (PBL) model in improving student learning outcomes in class X ecosystem material at SMAN 1 Lintau Buo Utara. This type of quantitative research, with a true experimental research design in the form of a pretest-posttest control group design. The population in this study was 354 consisting of 10 classes. The sampling technique used was random sampling technique. The research instrument created was a question that was validated by 3 validators consisting of 2 lecturers and 1 biology subject educator at SMAN 1 Lintau Buo Utara. The research results showed that learning outcomes increased in treatment group 1. There was an increase in N-Gain learning scores by 29.54%. The hypothesis was tested using the t-test with the help of the SPSS 25 program. Based on the t-test carried out with the help of the SPSS 25 program, Sig. (2-tailed) < 0.050, namely 0.000 on student learning outcomes, so the research hypothesis is accepted. So it can be concluded that the use of an integrated biology module with Minangkabau local wisdom using the Problem Based Learning (PBL) model on Ecosystem material is effective in improving student learning outcomes.